EIB Working Papers 2020/02 - Impact of FDI on economic growth The role of country income levels and institutional strength (Volume 2020/2) - Baiashvili, Tamar (2020)
The impact of foreign direct investment (FDI) on economic growth is affected by incomes levels and the quality of the institutional environment. This paper examines these relationships based on data for 111 countries, stretching back to 1980. It finds that FDI benefits do not accrue mechanically and evenly across countries. Instead, there is inverted-U shaped relationship between countries' income levels and the size of FDI's impact on growth. Moving from low to middle-income countries the effect gets larger. On the other hand, it diminishes again transitioning to high income countries. It also finds that absorptive capacity matters in channelling FDI effects. Within country income groups, countries with better-developed institutions relative to their peers benefit more from FDI in terms of growth.